Test of an Anxiety Sensitivity Amelioration Program for at-risk youth (ASAP-Y). (March 2020) - Knapp, Ashley A.; Feldner, Matthew; Allan, Nicholas P.; Schmidt, Norman B.; Keough, Meghan E.; Leen-Feldner, Ellen W.
Abstract: Objective: Adult research supports the efficacy of targeting the malleable risk factor of anxiety sensitivity (AS) in preventing anxiety and related psychopathology. However, very little work has evaluated the impact of AS reduction among youth, which is unfortunate given adolescence is a "core risk" period in terms of disorder onset. Method: The primary project aim was to test the effects of an Anxiety Sensitivity Amelioration Program for Youth (ASAP-Y) among a sample of 88 youth aged 10–14 years with elevated AS. High AS youth and a parent were randomly assigned to either the ASAP-Y, which consisted of psychoeducation and experimenter-led and parent-led exposures, or a general health information control condition. Results: Youth in the intervention condition sustained low AS levels across the intervention period, and although AS levels in both conditions decreased from baseline to the one-month assessment, this decrease was more pronounced at one-month for youth in the intervention condition. Further, significant indirect effects of condition on one-month anxiety and depression symptoms via reduced AS were detected. Homework compliance rates and self-report data support the acceptability of the ASAP-Y. Contrary to hypotheses, differences between conditions in emotional reactivity elicited using experimental psychopathology methods were not observed. Conclusions: The current findings offer preliminary support for the ASAP-Y as an acceptable selective preventive intervention for at-risk youth, with specific anxiety- and depression-related effects through reduced AS. Highlights: Intervention condition had greater decreases in anxiety sensitivity (AS) at 1-month. Indirect effects of condition on 1-month mood symptoms via AS were significant. Self-report and homework data supported the acceptability of the AS intervention. No differences between conditions were detected in challenge procedures outcomes.